RACIST MANIFESTATIONS IN PHYSICAL EDUCATION AND SCHOOL CLASSES (Fiep Bulletin - online, 2020)
This study addressed the issue of racism and racial prejudice in physical education classes at a municipal school in Porto Alegre, RS. It is part of the final Project of the doctoral thesis of the author with Universidad Internacional Iberoamericana de México-Unini Mx- and its main objective is the ethno-racial approach in the school context. One of the main variables in this study is the questiono of ethnic-racial nicknames as a way of denigrating black identity, not only in physical education classes, but throughout the school, demystifying these nicknames as simple jokes among classmates and framing them as cases racism and prejudice. The racial question has been wellstudied in Brazil, mainly through the historical struggle of the Unified Black movement and black intelectuais that adresses this question. The methodology used in the researched school, after extensive debate and stuydy with teachers, sutdents, parentes and Community in general, led us to the dialogical form, that is, whenever a case of racism, the teacher must stpo his and discuss the topic, listening and talking to the conflicting parties. Studies have pointed out that simply punishing the ofender did not solve the problem, as it often “empowers” the student even more. The dialogue remains the most effective way of discussing and combating these racista practices. The conversation with the discuss the topic, listening and talking to the conflicting parties. The results showed that dialogue remains the most effective way of discussing and combating these racist practices. The conversation with the offending student may trigger the processo raising awareness of the his or her disastrous atitudes, making him reflect that his practices are not jokes but rather forms of action of racism acting in the school environment.
Keywords: Racism; Racial Prejudice; awareness